2017
DOI: 10.17219/acem/62759
|View full text |Cite
|
Sign up to set email alerts
|

Kupffer cell in the immune activation and tolerance toward HBV/HCV infection

Abstract: Kupffer cells (KCs) are macrophages that are found in the sinusoids of the liver. KCs are a crucial part of the innate immune system, acting as scavengers and phagocytes. KCs and sinusoidal endothelial cells together form the first immune barrier of the portal system. Studies show that KCs can not only maintain homeostasis in the immune response, but also facilitate the pathogenesis of type B and type C hepatitis (HBV/HCV) through their antigen-presenting function and secretion of soluble mediators. KCs can ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…They maintain hepatic homeostasis during immune responses to liver injury and also function as central mediators of hepatic inflammation induced in response to microbial-derived products [1416]. The inflammatory cascade within the liver is initiated and propagated by KCs upon recognition of danger-associated molecular patterns (DAMPs) such as HMGB1 and pathogen-associated molecular patterns (PAMPs) such as viral RNA and/or viral proteins [17, 18]. Activated KCs produce and secrete a diverse array of chemokines and cytokines leading to leukocyte recruitment to the liver.…”
Section: Introductionmentioning
confidence: 99%
“…They maintain hepatic homeostasis during immune responses to liver injury and also function as central mediators of hepatic inflammation induced in response to microbial-derived products [1416]. The inflammatory cascade within the liver is initiated and propagated by KCs upon recognition of danger-associated molecular patterns (DAMPs) such as HMGB1 and pathogen-associated molecular patterns (PAMPs) such as viral RNA and/or viral proteins [17, 18]. Activated KCs produce and secrete a diverse array of chemokines and cytokines leading to leukocyte recruitment to the liver.…”
Section: Introductionmentioning
confidence: 99%
“…Polo et al, observed that hepatic damage induced by efavirenz involved acute interference with mitochondria, and similar observations have been made by other investigators (67,(71)(72)(73). The hepatic dysfunction associated with HIV infection and ART is likely to further accelerate the progression of HBV infection (63,74). It has been reported that hepatocytic mitochondrial dysfunction stimulates HBV gene expression through lipogenic transcription factor activation (74).…”
Section: Main Factors Associated With Hbv Infection In Plwhmentioning
confidence: 62%
“…As the largest population of resident macrophages in the liver, Kupffer cells play a key role in liver injury, hepatic inflammation, and clearance of HBV from the liver. The protective effects of Kupffer cells are due to their inherent role as innate immune cells (59)(60)(61)(62)(63). However, as these cells also express CD4+, CCR5, and CXCR4, they are vulnerable and can be productively infected by HIV, resulting in a dysregulated hepatic innate immune response, subsequent hepatic inflammation, and fibrosis (56,64,65).…”
Section: Main Factors Associated With Hbv Infection In Plwhmentioning
confidence: 99%
“…The liver has been traditionally described as a tolerogenic organ, with Kupffer cells (KCs) and dendritic cells representing the main cell subsets mediating tolerance. KCs suppress CD8 + T cell activity by several mechanisms, including overexpression of Fas-Ligand, which induces CD8 + T cell destruction (47); overexpression of PD-L1, which leads to cell exhaustion through PD-1 receptor on T cells (48); or secretion of IL-10, an immunosuppressive cytokine (49, 50). Although intrahepatic KCs have been shown in mice and rats to express TLRs (51, 52), those cells are hypo-responsive to endogenous LPS and also other TLR ligands (53).…”
Section: Discussionmentioning
confidence: 99%